KOMPONEN MAKNA UNGKAPAN METAFORIS DALAM PILEG 2009 DALAM WACANA SURAT PEMBACA DI HARIAN SUARA MERDEKA - Deli Nirmala (PAROLE: Journal of Linguistics and Education, 2010)
This paper is investigating the semantic components of the metaphorical expressions of letters to editors found in Suara Merdeka daily newspaper by  contrasting  the semantic features of the source and the target of the metaphorical expressions compared to those of the non-metaphorical expressions to find out the ground existing. Nonparticipant observation is used to collect and select the data. Referential identity and distributional methods with substitution and paraphrasing techniques are used to analyze the data. The result shows that the ground can be used to show the association of  the target and the source. The association can be elaborated by analyzing the diagnostic components of each domain. From the analysis, there are some association that can be shown among other things similarity in attributes, qualities, movement, and action.